STUDYING THE MOVEMENT OF A HORIZONTAL MOVING BODY TAKING INTO ACCOUNT THE RESISTANCE OF THE ENVIRONMENT AND SOLVING RELATED PROBLEMS - M. Dusmuratov; N. Allokulova; I. Polatova (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the causes of the precession movement of the Earth, the precession period, as well as astronomical and climatic changes caused by precessional motion.